Project-Based Learning and its Possibilities to Enhance the Teaching and Learning of English Focused on Cultural Identity Development - Bonifaz Castillo, Jennyfer Katherine (2025)
Project-Based Learning is an interactive approach that focuses its attention on learning through collaboration and creating real-world experiences. Furthermore, this active methodology helps students enhance their critical thinking and teamwork skills. The primary goal of Project-Based Learning (PBL) is to identify societal issues and develop solutions that allow learners to engage directly with their communities. Additionally, PBL encourages students to reflect on their cultural heritage and explore ways to express it using English as a foreign language. Given these aspects, this research project titled Problem-Based Learning and its Possibilities to Enhance the Teaching and Learning of English Focused on Cultural Identity Development" seeks to analyze the potential of PBL to enrich cultural identity development through English language teaching and learning. This research was developed under a qualitative approach, using a bibliographic matrix and a checklist as data collection instruments. Due to the nature of the investigation project, the population was taken from the bibliography. For this purpose, different databases such as E-Libro, Scielo, Scopus, and Web of Science were considered. Such sources were chosen as they contain papers, research, books, and information related to the field of education. The aforementioned instruments allowed analyzing the potential of Project-Based Learning to improve English language teaching and learning for the development of cultural identity. The results showed that Project-Based Learning (PBL) is a powerful tool that fosters cultural identity since it promotes constant interaction not only with peers and teachers but also with the environment. In this regard, students have the opportunity to understand in-depth the community’s lifestyle and the problems that affect them directly or indirectly. Likewise, the activities proposed in the pedagogical guide focus mainly on the development of cultural identity through the development of projects that involve a combination of theoretical knowledge and personal experiences.